Respiratory function in healthy long-term meditators: a systematic review - L. J. U. Karunarathne; W. A. D. L. Amarasiri; A. D. A. Fernando (Systematic Reviews, 2024)
Abstract Background There is a paucity of data on effects of long-term meditation on respiration. This systematic review summarized selected respiratory function parameters in healthy long-term meditators (LTMs) at rest, during meditation and their associations with meditation practice variables. Methods A systematic search of PubMed, EMBASE (Ovid), Scopus, Proquest Dissertation and Thesis Global databases, CENTRAL, and Google Scholar was performed from year 1950 to August 15th, 2023. Keywords “meditation,” “long-term meditation,” and respiratory/pulmonary/lung function and spirometry were used. Controlled-trials and observational studies exploring respiratory parameters in healthy LTMs published in English were included. Two independent reviewers selected studies, extracted data, and assessed the quality of the evidence. The Joanna-Briggs Institute Critical Appraisal Tools and the Single-Case Reporting Guideline In BEhavioural Interventions Statement were used to assess the methodological quality of the included studies. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Effect estimates of some outcomes were synthesized using alternative methods and data for other outcomes synthesized narratively as a meta-analysis was not possible. Results Nine studies comprising 3 case–control, 3 cross-sectional, and 3 single-subject study designs, involving 433 participants that met the eligibility criteria, were included. Two studies reported slower resting RR among LTMs compared to controls [SMD = − 2.98, 95% CI (− 4.48 to − 1.47), overall-effect (z-score) = 3.88 (p < 0.001), I 2 = 69%] with similar trend reported in the third study (MD = − 1.6, p = 0.053). Three studies reported slower RR in LTMs during meditation compared to baseline. Slower resting RR and mean RR change during meditation compared to baseline significantly negatively associated with meditation experience. PEFR was significantly higher in LTMs than controls [MD = 1.67, 95% CI (0.19–3.15), z-score = 2.21 (p = 0.03)]. No significant difference was observed in tidal volume [SDM = 0.93, 95% CI (− 1.13 to 2.99), z-score = 0.89 (p = 0.37), I 2 = 96%] and vital capacity [SDM = 1.25, 95% CI (− 0.45 to 2.95), z-score = 1.44 (p = 0.15), I 2 = 94%] of LTMs compared to controls. Conclusions Long-term meditation appears to be associated with slower baseline RR, and immediate reduction in RR during meditation, where greater practice amplifies the effects. Evidence on spirometry parameters in LTMs with ≥ 3 years of practice was limited.